Cold War Identities: Citizenship, Constitutional Reform, and International Law between East and West Germany, 1967–75. (October 2014) - Gehrig, Sebastian
Law became an important battleground in the Cold War between the two Germanys. In striving for international legitimacy, West Germany clung to ideas of legal continuity to the German Reich while the GDR bolstered the concept of an anti-fascist new beginning as its legal foundation. As national division continued, citizenship law became a tool for both German states in challenging the other Germany's authority over its respective citizenry. By the late 1960s, the GDR devised a citizenship law that effectively held East Germans hostage through the redefinition of citizenship. The GDR-citizenship law, moreover, repatriated former East Germans now living in the Federal Republic. The quest for legal supremacy thus profoundly affected ordinary Germans living east and west of the Iron Curtain. This article argues that the GDR government used citizenship and international law to its advantage in the attempt to pressure West Germany to recognize officially GDR sovereignty between 1967 and 1972. It demonstrates how the GDR forced the Federal Republic into action long before negotiations over Ostpolitik began in 1969. Citizenship law thus became a potent tool in the East German quest for international recognition and provoked intense responses in West German law-making.